The Key Success Factors for Smartphones VIVO Communication Technology Co. Ltd in Overseas Markets - Chengsheng Liu; Natalia Sakharchuk (Communications of International Proceedings, 2021)
With the increasing pace of internationalization and globalization of the world economy, companies have opened up access to international markets. This means that the business has received new opportunities to increase profits and influence. In this regard, national producers have begun to develop strategies for further behavior in order to capture new promising markets. To determine the optimal path for the company, it is necessary to determine the main success factors in the existing niche, as well as evaluate possible strategic solutions. This paper presents an analysis of the company VIVO Communication Technology Co. Ltd: the strengths and weaknesses, opportunities and threats, key success factors are highlighted, and a possible further development strategy is proposed.
Keywords: Strategic analysis; key success factors; competition; smartphones.